Virtual Game Learning Media to Understand the Types and Formation of High School Students Identities using the Vilamil Molina Method - Nasution, Muhammad Syahrul Azhari (Journal of Technology and Computer, 2025)
This study aims to address the challenges of conventional learning regarding the types and formation of self-identity among high school students by applying a virtual game as a learning medium. Conventional learning methods, such as lectures and textbooks, are often considered less effective in capturing students’ attention on personal topics like self-identity. Therefore, this research proposes the use of a virtual game combined with the Vilamil Molina Method to create a more interactive and engaging learning experience. The Vilamil Molina Method is a structured multimedia development approach that consists of five main stages: Development, Preproduction, Production, Postproduction, and Delivery. In the Development stage, the initial concept of an educational First Person Perspective (FPP) game application was formulated, targeting high school students. During the Preproduction stage, detailed designs such as Use Case Diagrams, Activity Diagrams, and Storyboards were created. The Production stage focused on implementing these designs by integrating a virtual museum environment and 3D objects using Unity. In the Postproduction stage, system testing was conducted through the Black Box method to ensure the application’s functionality. The final stage, Delivery, involved distributing the application to users for trial. The results of the study indicate that implementing a virtual game with the Vilamil Molina Method successfully created an effective learning medium. Functionality testing and user trials showed that the application worked properly, and the designed interactions functioned logically. By combining the entertainment elements of gaming with a systematic educational approach, this application is expected to improve high school students’ motivation, engagement, and understanding of self-identity formation in greater depth.